Asmeninės higienos reikmenys iš Vilniaus Žemutinės pilies Valdovų rūmų archeologinės medžiagos - Rėklaitytė, leva (Archaeologia Lituana, 2004)
In this article the author analyzes a variety of the items that were employed in the daily hygienic procedures among the residents of the Vilnius Lower Castle’s Palace during medieval and modem periods such as combs, razors, tweezers, earscoops, culters and tooth-brushes. The author observes that the tradition of the use of these instruments was known during considerably earlier periods of time as well. The Romans and Anglo-Saxons or the Iberian tribes were acquainted with a great variety of such items and not only with tweezers or combs but also with more sophisticated ones such as culters designated for a nail care or dentiscalpium and auriscalpium used as tooth and ear cleansers. The practice of the usage of these instruments didn’t cease with the fall of the Roman Empire as the concern of body cleanness was common among the Arab people who reached Europe in the 8th century and persisted there until the 15th century. The impressive diversity of the toilet items can be observed from the archaeological excavation material although at the same time the researchers note that the variety of stylistics of these goods make harder the assignation of their function as toilet or as surgical instruments. The artefacts from the Vilnius Lower Castle’s Palace represent an interesting set of toilet items that was designated to be used during ear, nail, teeth cleaning procedures and hair depilation. It’s easy to observe the different materials that were employed in their fabrication as bronze, wood or bone and horn. Furthermore, exists a clear difference in their realization way as some earscoops, for example, represent a meticulous and accurate artisan work, meanwhile the other ones reveal a rather rough made forms. In this respect it’s possible to claim the existence of the economical status representation through possession of the toilet items as prestigious objects fabricated from such precious materials as gold or silver. It’s interesting to observe that some toilet items could have shared two functions, for example, one sharp point of the artefact was designated for the care of ears and nails and the other one for picking one’s teeth. Especially interesting artefact is the representation of a bishop figure carved on one of these supposed earscoops although it is not possible to determine its function with certainty as only survives the upper part of the artefact. Apart from the earscoops other toilet items detected during the archaeological excavations in the Vilnius Lower Castle’s Palace are razors, tweezers and combs. The parallels regarding this type of artefacts can be observed not only among the excavation material from medieval sites in neighboring territories but also through the material analysis of all over medieval and modern Europe. One of the most interesting objects is the tooth-brush which analogue is known from the material of archaeological excavations in the old town of Vilnius. The author of the article tentatively proposes to date this artefact as belonging to the period not earlier as the 16th century. The affirmation of existence of concern of a body care among the residents of the Vilnius Lower Castle’s Palace during medieval and modem periods can serve as well – founded conclusion of this paper. The verification of this statement is the reveal of the use of different toilet items for this purpose. In this respect we can observe the use of similar artefacts as were used by Romans without a greater technological innovation.